Development of Chalcone-Derived Polyurethane and Hybrid Composites with Superior Thermal and Corrosion Resistance Properties - Umasankar, Poovizhi; Lakshmanan, Krishnan; Sivaramakrishnan, T.; Elango, G. (Asian Journal of Chemistry, 2026)
A chalcone-derived diol was synthesised and utilised for the production of polyurethane and its acrylic- and garnet-modified derivatives. The structural characteristics of the synthesised systems were elucidated via FT-IR and NMR studies, confirming the effective integration of urethane linkages, acrylic groups and garnet fillers. UV–Vis spectral study indicated π–π* and n–π* transitions in chalcone polyurethane, a bathochromic shift in acrylic polyurethane attributed to the extended conjugation and increased absorption in garnet polyurethane resulting from interfacial charge-transfer interactions. Thermal analyses (DSC, TGA and DTA) revealed that acrylic modification and garnet insertion enhanced crosslinking density, postponed degradation and elevated char yield, with garnet polyurethane displaying enhanced thermal resistance. Wettability study revealed a systematic transition from moderate hydrophilicity in chalcone polyurethane to increase the hydrophobicity in acrylic and garnet systems, due to surface alteration and filler-induced roughness. Electrochemical impedance spectroscopy validated the superior anticorrosive properties of garnet polyurethane, demonstrated by elevated charge transfer resistance and diminished ion diffusion. The findings collectively demonstrate that chalcone-derived polyurethanes, especially the garnet-reinforced composite, exhibit superior thermal stability, optical absorption, surface hydrophobicity and corrosion resistance, highlighting their potential as multifunctional protective coatings for advanced applications.